The mathematics curriculum from the perspective of the experts: scenes of the preparation of the curriculum proposal for the teaching of mathematics 1st. degree (São Paulo, 1980's) - Valente, Wagner Rodrigues (2022)
Studies on the curriculum, in particular on the mathematics curriculum, have been guided by analyzes that do not include investigations directly linked to the processes and dynamics involved in the systematization of knowledge for teaching and training teachers. For this, it is necessary to investigate the curricular documentation through historical studies, facing the challenge that the historian Jacques Le Goff (1996) called the transition from the analysis of monuments to documents. This article analyzes some aspects of the process of developing new knowledge for teacher training and for teaching mathematics, consolidated in the Curriculum Proposal of the state of São Paulo in the 1980s. With the direct election of new governors, there is a moment decisive step in the resumption of democracy. Thus, the period involves state policy initiatives to prepare educational documentation that could move away from times of military dictatorship. The study brings together empirical material from the experts who drafted the Proposal. It is concluded by showing new processes that started to include teachers and their experiences of pedagogical practices, reacting to the organization of mathematics organized for teaching systematized by experts.